Costing for universal health coverage: Insight into essential economic data from three provinces in Cambodia - Bart Jacobs; Kelvin Hui; Veasnakiry Lo; Michael Thiede; Bernd Appelt; Steffen Fleßa (Health Economics Review, 2019)
Background: Knowledge of the costs of health services improves health facility management and aids in health financing for universal health coverage. Because of resource requirements that are often not present in low- and middle-income countries, costing exercises are rare and infrequent. Here we report findings from the initial phase of establishing a routine costing system for health services implemented in three provinces in Cambodia. Methods: Data was collected for the 2016 financial year from 20 health centres (including four with beds) and five hospitals (three district hospitals and two provincial hospitals). The costs to the providers for health centres were calculated using step-down allocations for selected costing units, including preventive and curative services, delivery, and patient contact, while for hospitals this was complemented with bed-day and inpatient day per department. Costs were compared by type of facility and between provinces. Results: All required information was not readily available at health facilities and had to be recovered from various sources. Costs per outpatient consultation at health centres varied between provinces (from US2.33 to US4.89), as well as within provinces. Generally, costs were inversely correlated with the quantity of service output. Costs per contact were higher at health centres with beds than health centres without beds (US4.59, compared to US3.00). Conversely, costs for delivery were lower in health centres with beds (US128.7, compared to US413.7), mainly because of low performing health centres without beds. Costs per inpatient-day varied from US27.61 to US55.87 and were most expensive at the lowest level hospital. Conclusions: Establishing a routine health service costing system appears feasible if recording and accounting procedures are improved. Information on service costs by health facility level can provide useful information to optimise the use of available financial and human resources.
Keywords: 330; Health service costing system; Feasibility; Step-down allocation; Unit cost; Health Centre; Hospital